Integrating Digital-Based Differentiated Learning Media in a Single Platform to Enhance Students’ Motivation and Understanding of Social Arithmetic Concepts - Ni Wayan Gita Widya Rahayu; Sariyasa; I Wayan Puja Astawa (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This developmental research aims to produce digital based differentiated learning media designed to enhance students' motivation and conceptual understanding of social arithmetic. The development procedure employs the design research model, consisting of three phases: preliminary research, prototyping phase, and assessment phase. The subjects of this study were 34 seventh grade students at SMP Negeri 3 Mengwi. Data collection techniques included observations, interviews, questionnaires, tests, and documentation. The validity was verified by experts in media and material and learning, resulting in an average score of 4.65, categorized as very valid. The practicality level, based on student score on response questionnaires of 4.6 categorized as very practical and teacher response questionnaires, score of 4.7 categorized as very practical. The effectiveness of the media was assessed through improvements in learning motivation and conceptual understanding. Analysis of the learning motivation questionnaires showed a pretest score of 3.6 and a posttest score of 4.4, with an N-Gain value of 0.52 (medium category). Meanwhile, conceptual understanding test results indicated a pretest score of 61.47 and a posttest score of 81.47, with an N-Gain value of 0.52 (medium category). Effectiveness was determined through a one-group pretest–posttest design, indicating moderate improvement in both motivation and conceptual understanding.